Nanohibrids of LDH-AINES drugs: synthesis, characterization and stability properties - Mendieta, Silvia; Oliva, Marcos; Pérez, Celso; Herrero, Eduardo; Heredia, Angélica; Crivello, Mónica (5th Czech-Italian-Spanish Conference on Molecular Sieves and Catalysis, 2013)
Layered double hydroxides (LDH), also known as hydrotalcite like compounds or anionic clay, have technological importance in catalysis, optics, medical science and nanocomposite material engineering. Moreover, LDH are biocompatible materials, and may act as stable host matrices for storage and delivery of various intercalated bioactive molecules and drugs [1]. One important feature is that the labile bioactive substances intercalated into LDH could effectively be protected against rapid degradation by light, temperature, oxygen, alkali metals, etc. Indomethacin is a member of the NSAID. It is used to reduce pain involved in osteoarthritis, rheumatoid arthritis, bursitis, gout, etc., however, are well known side effects including gastrointestinal disturbance. The drug is described as poorly soluble and highly permeable (class II) drug. The MgAl-Indo samples have been prepared following direct synthesis by coprecipitation from Mg and Al chlorides; was added over a suspension with indomethacin [2]. The synthesis was prepared at different pH (8, 9 and 10) ± 0.2; the pH was maintained constant by continuous adding of 0.1 M NaOH. The coprecipitation was carried out at 35 °C under nitrogen atmosphere to avoid the incorporation of CO2. The resulting suspension was stirred for 20 h at 60 ºC under nitrogen atmosphere. The samples were characterized by X-ray powder diffraction, FT-IR spectra, Scanning electron microscopy, Thermogravimetric analyses and Differential scanning calorimetry analyses. Drug content was determined by UV absorption spectrophotometer Jasco 7800 at λ=320 nm. Successful intercalation of indomethacin into the LDH host is demonstrated by the XRD diagrams of the nano hybrids. On the other hand, the drug was absorbed on the surface of the LDH synthesized at pH 8 and 9. At pH = 10 showed higher order crystalline structure of LDH. The drug suffers a change of structure due to the heat treatments performed during the synthesis confirmed by FT-IR. The nanoclay confers more thermal stability to the drug observed by DSC; the decomposition temperature is enhanced about 100°C. The maximum incorporation was obtained with LDH synthesized at pH=8. The present results imply that the nano hybrids particles can be potentially used as a novel drug storage and delivery.
Keywords: LDH-AINES drugs